Pemanfaatan Delineator Jalan Dalam Mendukung Keselamatan Dan Ketertiban Lalu Lintas Di Desa Pasar Ngalam - Dirgo Hafiizh Danil; Khotimah Wahdaniyah; Melly Jayanti; Maudya Ramadhani; Marchell Febrian. G; Arifah Nur Fitriani; Panugra Kardiansya; Afri Melda; Dimas Aditya; Muhammad Naufal Aditya Lubis (CV. ITTC INDONESIA, 2026)
Traffic safety and orderliness are crucial aspects of establishing a safe, comfortable, and orderly transportation system, particularly in rural areas with limited traffic infrastructure. One measure to enhance road user safety is the use of road delineators devices that provide visual guidance to drivers, especially along road sections featuring curves, intersections, or conditions associated with a relatively high risk of accidents. This study aims to analyze the use of road delineators in supporting traffic safety and orderliness in Pasar Ngalam Village. The findings indicate that the installation of road delineators yields significant benefits by improving the visibility of road boundaries, helping drivers recognize the road's direction and conditions, reducing the potential for accidents, and fostering greater community awareness regarding orderly driving.